Religious Moderation as a Resolution in Responding to Social and Cultural Modernization in Indonesia - Rommy Muhammad Rijalul Fahmi; Asroruddin Lubis (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2026)
The acceleration of social and cultural modernization in Indonesia has had two impacts: on the one hand, it has strengthened the dynamics of social and cultural life, but on the other hand, it has given rise to challenges such as value divisions, identity conflicts, and religious polarization. This article analyzes how religious moderation can be a solution to address this modernization. Applying qualitative research methods focused on a literature review of primary sources (including documents in Arabic, English, and Javanese) and a critical analysis of the Indonesian context, this paper investigates the ability of religious moderation to bridge socio-cultural change and interfaith harmony. The research findings suggest that religious moderation, characterized by the principles of balance, inclusivity, and intercultural dialogue, has the potential to ease social tensions and maintain cultural diversity in a modernizing environment. However, the success of this moderation is highly dependent on factors such as institutions, religious education, and local cultural awareness. The implications of this research point to the need for increased literacy in pluralistic and culturally diverse religions, the development of moderation programs in digital platforms and local cultural contexts, and collaboration between religious leaders, civil society, and government institutions.